Prosedur Pemeriksaan Digital Subtraction Angiography (DSA) Vena Cerebral Dengan Akses Transradial Pada Kasus Cerebral Venous Thrombosis (CVT) - Sonia Josefa Fernandes; Suhariadi Atmanta; Kusman Kusman (STIKes Ibnu Sina Ajibarang, 2023)
Background: Cerebral venous thrombosis (CVT) is a form of stroke when blood clots develop in the (venous sinus) of the brain. This condition causes the blood that flows into the brain to be unable to flow out. This can cause reduced blood flow to the brain and damage or kill brain cells if not treated properly. The research aims to determine the digital subtraction angiography (DSA) examination procedure of cerebral veins with trans-radial access in cases of cerebral venous thrombosis (CVT). Method: This type of research is qualitative research with a case study approach. Data was collected on July 20 2023.The research subjects were doctors, interventional radiology doctors, and scrub nurses. By conducting observations, interviews and documentation of the implementation team involved. Results: From the results of observations, documentation and interviews with the implementing team, results were obtained regarding the Cerebral Vein Digital Subtraction Angiography (DSA) examination procedure with transradial access in cases of Cerebral Venous Thrombosis (CVT), including several sub-topics. The Cerebral Digital Subtraction Angiography (DSA) examination procedure with Transradial access is the right action for patients regarding immobility and shorter hospital stays. Conclusion: The Cerebral Vein Digital Subtraction Angiography (DSA) examination procedure with transradial access in cases of Cerebral Venous Thrombosis (CVT) includes patient preparation, tools and materials, examination techniques and post-action care. The Cerebral Vein Digital Subtraction Angiography (DSA) examination procedure with Transradial access is the right action for patients regarding patient immobility and shorter duration of hospital stay. The implementation team consists of a radiology specialist, a scrub nurse and no radiographers involved in the DSA examination room.